Magma Flow Rates and Temporal Evolution of the 2012–2014 Post‐Eruptive Intrusions at El Hierro, Canary Islands. Issue 12 (13th December 2019) - Benito‐Saz, Maria Angeles; Sigmundsson, Freysteinn; Charco, Maria; Hooper, Andrew; Parks, Michelle
Key Points: Models of magma flow rates are presented for six post‐eruptive magmatic intrusions under El Hierro volcano from June 2012 to March 2014 Initial magma flow rates of 300 m 3 /s decaying exponentially with time are inferred using GPS and InSAR, and a Bayesian inversion approach A deep magma body likely fed the inferred sill‐like intrusions with a conduit to a common feeding point under the center of the island Abstract: The 2011–2014 volcanic activity at El Hierro (Canary Islands) was characterized by a 5‐month long submarine eruption as well as a series of magmatic intrusions occurring between 5 months and 2 years after the eruption, as revealed by seismic swarms and ground deformation. We study the temporal evolution of the six post‐eruptive magmatic intrusions, using Global Navigation Satellite System and Interferometric Synthetic Aperture Radar observations complemented with relocated earthquakes. Magma volumes and magma supply rates are determined from inversion of the geodetic data using a Bayesian approach. The intrusions last between 3 and 20 days and are inferred to be sill‐like, thin compared with their lateral extent and emplaced in the 13–16 km depth range. Initial magma flow rates of 300 m 3 /s decay exponentially with time. The two largest intrusions occurred in June–July 2012 and March–April 2013. During each of these events, magma migrated laterally, and >120 ×10 6 m 3 of magma was intruded beneath the island. The shortest events, <1 week‐long, intruded (24hyphen;44) ×10 6 m 3 of magma beneath the volcano. We suggest that all intrusions originated from an overpressure in a deep magma body located beneath the center of El Hierro. The crust/mantle boundary and the previous intrusion that fed the 2011–2012 submarine eruption may have discouraged the ascent of the post‐eruptive intrusions to the surface and forced them to migrate laterally away from the island as sill‐like sources.